Influence of Soaking and Sprouting on the Colour Kinetics of White Sorghum Grains - Huirem, Boris; Sahoo, Pradeepta Kumar (Annals of Arid Zone, 2024)
Colour is a critical sensory quality parameter reflecting the final quality of various food grain products. This study investigated the impact of different soaking durations (6, 12, 18, and 24 hours) and sprouting periods (24, 36, 48, 60, and 72 hours) on the color degradation kinetics of white sorghum grains. Colour parameters such as lightness (L*), redness/greenness (a*), yellowness/blueness (b*), total colour change (ΔE), and browning index (BI) were measured. These experimental values were fitted to four selected models (Zero-order, First-order, Power, and Quadratic) using MATLAB R2019a’s non-linear regression tools. Comparing the soaked and sprouted samples, the soaked grains exhibited superior colour characteristics, with higher lightness values that are favourable for milling, whereas the sprouted samples showed increased redness and browning index values. The results indicated that the Quadratic equation best described the color changes in both soaked and sprouted sorghum samples.